A case study for the software size estimation through MK II FPA and FP methods. (2016) - Borandag, Emin; Yucalar, Fatih; Erdogan, Senol Z.
Software size estimation is one of the most crucial and daunting tasks for a software project manager. It is very important for the accurate planning and calculation of the software project. The importance of software size estimation becomes critical at the beginning of the software life cycle. Software size estimation is a basic input for the software effort and cost estimation. There are many different approaches and various methods for software size estimation up to now such as the function points method, e.g., IFPUG FPA, Mk II FPA, COSMIC FFP. In this paper, the size of the software project was calculated through the function points method and Mark II FPA. The same software project was implemented by different software development teams. Early estimations were performed for the software project and the data obtained as a result of the teams' studies were compared.